Polineoplasia in patients with cervical cancer in the Chelyabinsk region of Russia - S. A. Bekhtereva; A. S. Domogirova; A. V. Vazhenin; I. A. Aksenova (Исследования и практика в медицине, 2018)
The purpose of the study was to analyze the incidence of primary-multiple cancer (PMC) of the female reproductive system according to the population cancer register of the Chelyabinsk region for 15 years (1999-2013) using the example of PMC of the cervix. Carry out an analysis of the adjusted cumulative survival in the group of patients with PMC of the cervix as compared with solitary cervical cancer.Material and methods. The material was processed using the classification of Zisman I. F. and Kirichenko G. D. (1978) on the sequence of tumors: metachronous, synchronous, mechatronic-synchronous and synchronous-metachronous. The interval of metachronousness is 6 months. The survival rates of cancer patients in the Chelyabinsk region were calculated automatically with the use of the computer program "Calculation of survival rates" — an application to the population-based cancer registry of OOO Novell-SPb. Using the method of continuous sampling, we carried out a retrospective analysis of the case histories of patients with PMC of the female reproductive system treated in the SBEO CRCOD for 15 years (1999-2013).Results. During the period under review, 82 patients with PMC of the cervix uteri were examined, metachronous tumors prevailed in 55 (67.1%), synchronous tumors developed in 27 (33.75%). In the group of metachronous tumors in 12 (21.8%) patients had a combination of three tumors. Three (5.45%) patients had a combination of four tumors. Analysis of combinations of cervical cancer showed that more often, the cervical cancer metachronically met with breast cancer 35% (14 patients), endometrial cancer 17.5% (7 patients), ovarian cancer 7.5% (3 patients). Synchronously cervical cancer was more often combined with breast cancer 42.8% (9 patients), endometrium 28.6% (6 patients), ovaries 23.8% (5 patients) and rectal cancer 4.8% (1 patient).The results of calculation of the index of the adjusted cumulative survival of the study group of the PMC of the cervix showed that in the group of metachronous tumors, survival rates were significantly higher than in the group of synchronous tumors: single-year survival was 84.8 ± 6.3% against 82.4 ± 9.2, three-year survival — 66.8 ± 7.8% against 47, 1 ± 12.1, and five years after the diagnosis, 53.8 ± 8.6% of patients survived.Conclusion. Thus, patients with cervical cancer are at risk of developing cancer of other localizations that share common etiopathogenetic factors, such as HPV infection in women, hormonal disorders.